Transport in Victorian Times - Stephen, Margaret; Edited by Brown, Carron (England Wayland, 1998)
Looks at transport in the time of Queen Victoria, including canals, railways, steamships, bicycles and the first cars.
Include Colour Illustrations, Glossary and Index
Keywords: Manners and customs -- Transportation -- Great Britain